Fanning the Flames or a Troubling Truth? The Politics of Comparison in the Israel-Palestine Conflict. Issue 4 (2nd October 2019) - Turner, Mandy
ABSTRACT: The politics of comparison in the Israel-Palestine conflict is largely encapsulated in the use of two analogies. The first is the 'Holocaust-Hitler analogy' used by Israel and its supporters, which portrays Israel as a beleaguered nation surrounded by Nazi sympathisers who seek to destroy it as the Jewish homeland. The second is the 'apartheid analogy', which compares the conflict to that of Apartheid-era South Africa and portrays Palestinians as being the victims of racism and settler colonialism. This article analyses why, how and with what desired impact these two comparisons are invoked.